Investigating the Relationship of Financial Hardships with Postpartum Depression in Maternal Health of Pakistani Women: A Cross-Cultural Study (Journal of Social Sciences Review, 2025)
The aim of this study is to investigate the impact of financial hardships on postpartum depression among Pakistani women. In Pakistan, many women face postpartum depression during and after their pregnancies once or twice but receive very little care in hospitals and homes, which is alarming. Many women are not financially stable, and that's why they don't go for postpartum therapy. In fact, many women face financial hardships during pregnancies, and this issue leads to postpartum depression as well. This was a quantitative, descriptive, correlational research design. For this study, more than 150 females were requested to fill out the questionnaires via online and face-to-face meetings and finally received 103 (from Peshawar, Islamabad, and Lahore) complete responses, so the retrieving rate was  68.7%. The results of the current study stated that the relationship between financial hardships and postpartum depression in maternal health is positive and significant. This study is of great theoretical significance from the Pakistani perspective and of practical significance because it will help medical health practitioners design policies to reduce the financial hardships for women to improve their health during maternity.
Keywords: Postpartum Depression; Maternal Health; Financial Hardships; Regression Analysis; Correlation Analysis